The industrialisation of South Africa s creative economy: The role of creative intermediaries - Ferreira, Carla (Graduate School of Development Policy and Practice, 2024)
There is an increasing emphasis on the creative economy's convergence of cultural, social, and economic development agendas on the African continent. Africa's creative economy is a potentially viable source for development on both country-specific and continental levels. Studying creative intermediaries as mid-level actors is a plausible way to gain insight into a specific creative ecosystem. This approach allows for the exploration of the activities of creative and cultural practitioners representing the micro-level of sectoral activity whilst also reflecting on the policy frameworks which creative intermediaries operate in. South Africa's creative economy has been proven to support inclusive economic development, but the sector's impact is often undermined by outdated policy frameworks and failed public programmes. The sector is also further burdened by delayed policy reforms and an insufficient national creative infrastructure to adapt to rapid changes in technological advancements, which is intimately linked to the value chain of many creative goods and services in various ways. This study pursued the research question of how creative intermediaries can facilitate the industrialisation of South Africa's creative economy. Industrialisation is a key mechanism for economic growth. It entails the integration of various factors in the production process to ultimately increase productivity and result in more complex activities. This study focussed on South Africa's creative economy and studied the creative ecosystem of independent and prominent creative organisations based in the Western Cape. This study built on the grand theory of developmentalism in the context of a developing country and provided a framework for the industrialisation of an unconventional product. The research relied on a mixed method research approach based on complementarity. The research design was cross-sectional, and the sampling strategy was that of convenience. This research found an extreme disconnect between the public sector and the rest of the creative ecosystem within the Western Cape. This study also identified creative intermediaries as a viable way to increase citizen trust and social mobility. A credible growth trajectory can, therefore, be created through improved governance, addressing persistent inequality, creating employment opportunities and the expansion of public initiatives which can all be facilitated through creative intermediaries. The industrialisation of South Africa's creative economy can be aided by an embedded private-public sector, to firstly, ensure a well-informed state, and secondly to design industrial policy to motivate structural change and capacity building to aid policy inventions. This study also redefined the term creative intermediary to consists of three dimensions which enables the entity to act as agents of change. This is specific to the context of a developing country in which industrial policy needs to be designed to ensure inclusive development.